Forklift balancing weight with adjustable gravity center - ZENG LIJIAO (2021)
The invention discloses a forklift balancing weight with the adjustable gravity center. The forklift balancing weight comprises a portal, a forklift ram is movably connected to the interior of the portal, a rotating disc is fixedly connected to the bottom of the portal, a bottom plate is rotatably connected to the bottom of the rotating disc, an inserting rod is fixedly connected to one side of the bottom plate, and rolling wheels are fixedly connected to the bottom of the bottom plate; and the outer walls of the rolling wheels are in sliding connection with the interiors of sliding grooves formed in the upper surface of a base. According to the forklift balancing weight with the adjustable gravity center, by rotating the output end of a motor, a conveying belt drives a connecting rod and the bottom plate to start to move, the rolling wheels fixedly connected with the bottom of the bottom plate slide in the sliding grooves formed in the upper surface of the base, and a hydraulic telescopic rod moves left and